Hospitality in Deconstruction Thought - Nigro Solis, Dirce Eleonora (Disertaciones, 2020)
The theme of hospitality has been sufficiently analyzed by Jacques Derrida, the French thinker of deconstruction. This article intend to investigate hospitality considering the radical opposition, the aporia, between The Law of unconditional hospitality in its universal singularity and the laws of conditional hospitality. Who is able to give or to receive hospitality? Someone who says his name? A person of rights? A foreigner? We will explore some of the conditions to answer to this: hospitality as a question of place, as a question of language and as a question of name.